Muscle strength field-based tests to identify European adolescents at risk of metabolic syndrome: The HELENA study. Issue 8 (August 2019) - Castro-Piñero, José; Laurson, Kelly R.; Artero, Enrique G.; Ortega, Francisco B; Labayen, Idoia; Ruperez, Azahara I.; Zaqout, Mahmoud; Manios, Yannis; Vanhelst, Jeremy; Marcos, Ascension; Polito, Angela; Gonzalez-Gross, Marcela; et al.
Abstract: Objectives: To determine whether handgrip strength (HG) and/or standing long jump (SLJ) are capable of detecting risk of metabolic syndrome (MetS) in European adolescents, and to identify age- and sex-specific cut points for these tests. Design: Cross-sectional study. Methods: Participants included 969 (aged 12.5–17.5 years old) adolescents from 9 European countries ( n = 520 girls). Absolute and relative HG and SLJ tests were used to assess upper and lower muscle strength, respectively. MetS status was determined using the age- and sex-specific cut points proposed by Jolliffe and Janssen´s, Additionally, we computed a continuous cardiometabolic risk index with the average z-score of four cardiometabolic risk factors: Wait circumference, mean arterial pressure, triglycerides/high-density lipoprotein cholesterol, and fasting insulin. Results: The prevalence of MetS was 3.1% in European adolescents. Relative HG and absolute SLJ were the best tests for detecting the presence of MetS (Area under the receiver operating characteristic ( AUC ) = 0.799, 95%CI :0.773–0.824; and AUC = 0.695 95%CI :0.665–0.724), respectively) and elevated cardiometabolic risk index ( AUC = 0.873, 95%CI :0.838–0.902; and AUC = 0.728 95%CI :0.698–0.756), respectively) and, regardless of cardiorespiratory fitness. We provide age- and sex-specific cut points of upper and lower muscle strength for European adolescents to identify the presence of MetS and elevated cardiometabolic risk index. Conclusions: The proposed health-related cut points could be used as a starting point to define health-related levels of upper and lower muscle strength in adolescents. Likewise, the diagnostic statistics provided herein can be used to offer feedback to adolescents, parents, and education and health professionals about what it means to meet or fail test standards.